The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s1516-14392012005000086
|View full text |Cite
|
Sign up to set email alerts
|

Carboxylated nitrile butadiene rubber/hybrid filler composites

Abstract: The surface properties of the OSW and NLS are measured with the dynamic contact-angle technique. The x-ray photoelectron spectroscopy (XPS) of the OSW reveals that the OSW possesses various reactive functional groups namely hydroxyl groups (OH). Hybrid filler from NLS and OSW were incorporated into carboxylated nitrile rubber (XNBR) to produce XNBR hybrid composites. The reaction of OH groups from the OSW with COOH of the XNBR is checked by attenuated total reflectance spectra (ATR-IR) of the composites. The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…The incorporation of industrial and agricultural waste such as olive solid by‐product, marble waste, rice husk, and agro polymer based olive solid as hybrid fillers in rubber nanocomposite were reported . The incorporation of agro polymer‐based olive solid waste into the carboxylated nitrile rubber (XNBR)–organoclay (Nanofil 15) nanocomposites had improved the mechanical properties compared to XNBR/organoclay as well as XNBR gum vulcanizate . Relative efficiency of different types of fillers (phenolic resin, CB and CB plus phenolic resin) hybrid system in nitrile rubber (NBR) vulcanizates for the improvement of physico‐mechanical properties, resistance to swelling in oil/fuel and thermal stability has been studied .…”
Section: Introductionmentioning
confidence: 99%
“…The incorporation of industrial and agricultural waste such as olive solid by‐product, marble waste, rice husk, and agro polymer based olive solid as hybrid fillers in rubber nanocomposite were reported . The incorporation of agro polymer‐based olive solid waste into the carboxylated nitrile rubber (XNBR)–organoclay (Nanofil 15) nanocomposites had improved the mechanical properties compared to XNBR/organoclay as well as XNBR gum vulcanizate . Relative efficiency of different types of fillers (phenolic resin, CB and CB plus phenolic resin) hybrid system in nitrile rubber (NBR) vulcanizates for the improvement of physico‐mechanical properties, resistance to swelling in oil/fuel and thermal stability has been studied .…”
Section: Introductionmentioning
confidence: 99%
“…lignocelluloses, it is intended to apply this material into polyamide PA-12 which is a kind of polar engineering material due to their amide group (--CONH--).Among various classes of polyamides PA12 has a lower melting temperature compared to other types such as PA6 etc. [11][12][13]. The melting temperature of PA 12 is also lower than the degradation temperature of wood material compared to other commercially available polyamides.…”
Section: Introductionmentioning
confidence: 99%
“…This has opened a track to recycle industrial wastes, such as pulverized fuel ash and ferrous metallurgical by‐products, such as slag, which is a mixture of oxides. Based on the fact that naturally occurring minerals, such as kaolin, clay, and feldspar, are widely used in the polymer‐based composites , it could be concluded that slag which is a mixture of oxides could also used as a reinforcement for polymer composites. In this regard, only few studies on the use of slag as filler in polymer composites are available in the literature .…”
Section: Introductionmentioning
confidence: 99%